COVID-19 and antiphospholipid antibodies: A position statement and management guidance from AntiPhospholipid Syndrome Alliance for Clinical Trials and InternatiOnal Networking (APS ACTION). (December 2021) - Wang, Xin; Gkrouzman, Elena; Andrade, Danieli Castro Oliveira; Andreoli, Laura; Barbhaiya, Medha; Belmont, H Michael; Branch, David Ware; de Jesús, Guilherme R; Efthymiou, Maria; Ríos-Garcés, Roberto; Gerosa, Maria; El Hasbani, Georges; et al.
Coronavirus disease 2019 (COVID-19) is associated with a high rate of thrombosis. Prolonged activated partial thromboplastin times (aPTT) and antiphospholipid antibodies (aPL) are reported in COVID-19 patients. The majority of publications have not reported whether patients develop clinically relevant persistent aPL, and the clinical significance of new aPL-positivity in COVID-19 is currently unknown. However, the reports of aPL-positivity in COVID-19 raised the question whether common mechanisms exist in the pathogenesis of COVID-19 and antiphospholipid syndrome (APS). In both conditions, thrombotic microangiopathy resulting in microvascular injury and thrombosis is hypothesized to occur through multiple pathways, including endothelial damage, complement activation, and release of neutrophil extracellular traps (NETosis). APS-ACTION, an international APS research network, created a COVID-19 working group that reviewed common mechanisms, positive aPL tests in COVID-19 patients, and implications of COVID-19 infection for patients with known aPL positivity or APS, with the goals of proposing guidance for clinical management and monitoring of aPL-positive COVID-19 patients. This guidance also serves as a call and focus for clinical and basic scientific research.